The Wrestler's Many Years of Technical and Tactical Training (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This study explores the long-term technical and tactical training processes in wrestling, addressing the knowledge gap in optimizing training methodologies for sustained athletic excellence. Utilizing a systematic review of pedagogical approaches and empirical data, the research examines the progression of training stages from foundational techniques to high-performance mastery. Findings indicate that structured, age-specific training significantly enhances skill acquisition, endurance, and competitive readiness. Results highlight the importance of adaptive coaching strategies in optimizing physical and tactical development. The study's implications suggest refining training programs to maximize wrestler performance and longevity in competitive sports.